2019
DOI: 10.18488/journal.70.2019.62.61.78
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic Practices of Maize and Farm Nutrient Status in Bako Tibe District, West Shoa Zone, Ethiopia: Lesson from Agronomic Panel Survey

Abstract: Agronomic panel survey was conducted in Bako Tibe district to assess current farmers maize agronomic practices and associated actual maize grain yields. The survey was conducted using 100 households. Most of the maize farms (90%) were characterized as having strongly to strongly acidic soils, low to medium SOC, medium to high TN, very low to low av.P, high to very high exch. K, low to medium exch.Ca, and medium to high exch. Mg, high av. Zn and Fe and very high Mn contents. Most farmers (94%) grow improved mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…Insufficient nutrient application results in slow development and delayed silking (Gurmu et al, 2020). The result was in line with Balemi et al (2019) and Bakala (2018), who reported that as the rate of application of blende NPS fertilizer increased, there was a reduction in the number of days to 50% in maize crops. Days to 90% maturity: Days to 90% maturity was significantly (p 0.05) influenced by the interaction and the Main effects (p 0.01) of blended NPS fertilizer and betweenrow spacing.…”
Section: Phonological and Growth Parameterssupporting
confidence: 79%
See 4 more Smart Citations
“…Insufficient nutrient application results in slow development and delayed silking (Gurmu et al, 2020). The result was in line with Balemi et al (2019) and Bakala (2018), who reported that as the rate of application of blende NPS fertilizer increased, there was a reduction in the number of days to 50% in maize crops. Days to 90% maturity: Days to 90% maturity was significantly (p 0.05) influenced by the interaction and the Main effects (p 0.01) of blended NPS fertilizer and betweenrow spacing.…”
Section: Phonological and Growth Parameterssupporting
confidence: 79%
“…The idea is similar to that of Khan et al (2017), who found that increasing plant population density increased plant height. Balemi et al (2019) also found that increasing the application of blended fertilizers with smaller between-row spacing significantly increases plant height. While sparsely populated plants intercepted enough sunlight to promote lateral growth, the plant's height became medium.…”
Section: Phonological and Growth Parametersmentioning
confidence: 84%
See 3 more Smart Citations